Current Perspective in Mixed Pain - Guillén-Núñez, María del Rocío; Juárez-Lemus, Angel Manuel; Hernández-Porras, Berenice Carolina; Hernández-Rodríguez, Daniela (Journal of Drug Delivery and Therapeutics, 2024)
Pain is one of the 10 leading causes of medical consultation worldwide and is the alarm symptom of the organism in situations that threaten its integrity, however, when it becomes chronic, it loses its protective capacity and becomes, in many cases, the disease itself. According to the International Association for the Study of Pain (IASP) pain is classified as nociceptive, neuropathic and nociplastic. Mixed pain has been described years ago due to the coexistence of different types of pain. We can conclude that we do not have a screening tool and/or treatment algorithm for mixed pain, so it is preferable that pain management begins with a rigorous assessment, using the latest available tools, followed by individualized evidence-based treatment with multimodal therapy when appropriate. Keywords: nociceptive pain, neuropathic pain, mixed pain.